Knowledge of chronic kidney disease and dialysis care among nurses at a hemodialysis centre in southern Iraq - Thani Asmar Radhi; Mariam Hasan Hafedh; Aqeel Azeez Arrar; Haider Ali Hussein; Abdulmalik Fareeq Saber (Discover Public Health, 2026)
Abstract Background and aim Hemodialysis nursing is a high-stakes, technology-dependent specialty whose safety depends on bedside knowledge of chronic kidney disease (CKD) and its renal-replacement therapies. Knowledge deficits in CKD pathophysiology, dialysis prescription, and complication recognition have been linked to measurable patient harm in low- and middle-income settings. This exploratory study aimed to assess hemodialysis-unit nurses’ knowledge regarding CKD and dialysis-related care, and to identify demographic and training-related correlates of preparedness, at the Misan Dialysis Center in Al-Sadder Teaching Hospital, Misan Governorate, Iraq. Method A descriptive cross-sectional study was conducted from October 10, 2023, to May 1, 2024, at the Misan Dialysis Center. A census approach was used: every nurse working in the unit and meeting the eligibility criteria was invited, and no sampling was performed. After exclusion of 10 pilot-study nurses, the final sample comprised 38 nurses with at least one year of nephrology nursing experience and current assignment to the hemodialysis unit. Data were collected using a structured, self-administered Arabic-language questionnaire covering demographic and professional characteristics and a 20-item knowledge assessment of CKD and dialysis-related care. Statistical analyses included descriptive statistics, Chi-square tests, Pearson and Spearman correlations, hierarchical multiple linear regression, and binary logistic regression. Given the sample size, all multivariable models are reported as exploratory. Results A total of 38 hemodialysis-unit nurses participated (mean age 24.6 ± 4.2 years; median 5.0 years of nursing experience, IQR 3.0–8.0). Findings revealed an overall moderate but clinically insufficient level of knowledge with a mean of 0.48 ± 0.126; 81.6% of nurses fell within the moderate band, 13.2% within the poor band, and only 5.3% within the good band. Critical knowledge deficits were identified for phosphorous restriction (86.8% incorrect), antidiuretic hormone and interdialytic fluid balance (86.8% incorrect), and the leading cause of death in CKD (78.9% incorrect). Hierarchical regression demonstrated that personal, experience-and-training, and hemodialysis-specific variables together explained 53.4% of variance (Adjusted R² = 0.448). Logistic regression showed that recent refresher (OR = 5.01), bachelor-or-higher education (OR = 4.00), and prior training (OR = 3.37) were the strongest correlates of adequate knowledge, with the model achieving 84.2% correct classification (AUC = 0.892). Conclusions Hemodialysis-unit nurses at the Misan Dialysis Center demonstrated measurable preparedness gaps in the CKD and dialysis knowledge domains assessed. Because this was a single-centre study of 38 nurses, and because the instrument did not assess vascular access care or infection control, the findings are preliminary and describe this unit rather than Iraqi dialysis nursing generally. Structured, hemodialysis-specific refresher curricula and competency-based remediation merit evaluation, and the preparedness framework presented here requires prospective validation before any use in staffing or supervision decisions.